Trainer's Motivation to Follow the National Level 1 Physical Coach Training in Stok Bina Guna (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This research is quantitative descriptive. The method used in this research is a survey method. The instrument used is a questionnaire. The instrument that has been arranged is consulted with the expert, then the validity test is carried out with the results that 12 items fall out of 56 items in the questionnaire statement so that there are 44 statement items and the reliability is 0.936. The population in this study were coaches of all sports a total of 47 people. The data analysis technique used is descriptive analysis with percentages. The results showed that the motivation of the trainers to take part in the national level 1 physical training at STOK Bina Guna was in the category of 8.5% having very low motivation to take part in the national level 1 physical training, 8.5% having low motivation.